Development and evaluation of Novasomal drug delivery system using natural polymer for ocular drug delivery - S Pathare, Yogyata; S Tare, Manoj; S Pathare, Sandeep; Deshpande, Shweta (Journal of Neonatal Surgery, 2025)
Novasomes are a type of novel vesicular drug delivery system that are structurally similar to liposomes but offer enhanced stability and encapsulation efficiency. Novasomes are composed of nonionic surfactants, cholesterol, and free fatty acids, allowing them to exhibit a high degree of deformability and resilience. The purpose of this research article was to develop curcumin loaded novasomes for ophthalmic delivery. It aims to enhance drug corneal permeation and to improve its antimicrobial activity. Also, sustain release effect of the formulation is studied. Ethanol injection method was used to formulate Curcumin loaded novasomes. The researched factors were SPAN 80, CMTG and its effect on particle size (PS), Poly-dispersity index (PDI) Zeta potential (ZP), In-vitro drug release was studied. Numerical optimization by Design-Expert® software was employed to select the optimum formula. Additional evaluation of stability studies, drug permeation and anti-microbial activity studies were also performed. Zone of inhibition were observed around E.coli and S .aureus each having the diameter 2.90 cm and 3.24 cm respectively indicates that the formulation has good antibacterial activity. The study indicated Curcumin retained its antimicrobial activity when formulated as a curcumin loaded novasome forming ophthalmic system against both selected S. aureus and E. coli. Hence, the developed formulation is a viable alternative to conventional eye drops by virtue of its ability to enhance bioavailability through its longer precorneal residence time and ability to sustain drug release.